Poverty Reduction Strategies and Cultural Values in Indonesia's Northern Coastal Communities: Trends, Interventions, and Local Wisdom - Zuber, Ahmad (MUHARRIK: Jurnal Dakwah dan Sosial, 2024)
This study aims to analyze the trend of changes in the poverty level of rural communities in the northern coastal area of Demak in the last two years, identify strategies to increase the economic added value of the poor in the region, and understand local cultural values that can be used to overcome poverty. This study uses a descriptive qualitative approach with a purposive sampling method. The data is analyzed through domain analysis and classification. The study results show that the poverty rate in the northern coastal region of Betahwalang has decreased in the last two years, which is characterized by infrastructure improvements, increased asset ownership, and diversification of livelihoods. Strategies to increase the economic added value of people experiencing poverty include education, training, debriefing, processing industry development, and capital provision. Local cultural values supporting poverty alleviation include faith, honesty, hard work, independence, and cooperation.